2020
DOI: 10.21608/sjfop.2020.114565
|View full text |Cite
|
Sign up to set email alerts
|

IMPACTS OF COMPOST, BIOFERTILIZER AND/OR SOME ANTIOXIDANT TREATMENTS ON GLADIOLUS (GLADIOLUS GRANDIFLORAS) B. Corms and cormels production and some chemical constituents

Abstract: Gladiolus is commercially propagated by its underground structure for production of flowers and corms as well as cormels. A field experiment was conducted during two successive seasons of 2018/2019 and 2019/2020 to investigate the effects of compost as an organic fertilizer (0, 5, 10 and 15 ton/fed) and Microbein biofertilizer (M.B.) at 50 ml/plant and/or some antioxidant treatments (salicylic and ascorbic acids) on corm and cormels production and chemical constituents of Gladiolus grandiflorus var. Jester pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…The current finding proved that geranium plant growth, flowering attributes, ion percentage, and chlorophyll concentration significantly increased by application of either biofertilizer or chemical fertilizer with or without compost addition. These findings are in line with earlier studies that indicate the effects of the application of chemical fertilizer [28,29], compost [14,15,17], and biofertilizers [7,14].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The current finding proved that geranium plant growth, flowering attributes, ion percentage, and chlorophyll concentration significantly increased by application of either biofertilizer or chemical fertilizer with or without compost addition. These findings are in line with earlier studies that indicate the effects of the application of chemical fertilizer [28,29], compost [14,15,17], and biofertilizers [7,14].…”
Section: Discussionsupporting
confidence: 93%
“…Attia et al [44] also showed that the use of different biofertilizers planted with Polianthes tuberosa plants led to an improvement in the characteristics of flowering growth, represented by the number of flowers per inflorescence, the length of the inflorescence, the dry weight of the inflorescence, and the diameter of the flower. Hassan and Abd El-Azeim [14] also found that the application of biofertilizers resulted in a significant increase in the characteristics of inflorescence length, inflorescence wet and dry weight, number of flowers/inflorescence, and flower diameter of Gladiolus plants. These encouraging effects may result from increasing nutrient availability [45]; accelerating cell expansion and division via the synthesis and action of auxin, cytokinin (CK), and gibberellin (GA) [46]; and accelerating atmospheric N fixation, which is required for nucleic acid, protein, and chlorophyll synthesis along with enhancement of the photosynthetic rate and plant biomass accumulation and flowering attributes [47].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations